2021
DOI: 10.3390/nu13020525
|View full text |Cite
|
Sign up to set email alerts
|

Do Only Calcium and Vitamin D Matter? Micronutrients in the Diet of Inflammatory Bowel Diseases Patients and the Risk of Osteoporosis

Abstract: Osteoporosis is one of the most common extraintestinal complications among patients suffering from inflammatory bowel diseases. The role of vitamin D and calcium in the prevention of a decreased bone mineral density is well known, although other nutrients, including micronutrients, are also of extreme importance. Despite the fact that zinc, copper, selenium, iron, cadmium, silicon and fluorine have not been frequently discussed with regard to the prevention of osteoporosis, it is possible that a deficiency or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…These vitamins and nutrients are inevitable for the growth, development, and proper functioning of the human body. Deficiency of these micronutrients for a short period does not cause much harm but their shortage for a long time may cause many diseases like anemia (Fe deficiency), beriberi (Vitamin B deficiency), pellagra (niacin deficiency), rickets (vitamin D deficiency), and scurvy (vitamin C deficiency) or be fatal (Table 1) (34,35). Approximately 25% of the world's population suffers from anemia and Fe deficiency is its leading cause (50-60% affected).…”
Section: Malnutrition-a Hidden Hungermentioning
confidence: 99%
“…These vitamins and nutrients are inevitable for the growth, development, and proper functioning of the human body. Deficiency of these micronutrients for a short period does not cause much harm but their shortage for a long time may cause many diseases like anemia (Fe deficiency), beriberi (Vitamin B deficiency), pellagra (niacin deficiency), rickets (vitamin D deficiency), and scurvy (vitamin C deficiency) or be fatal (Table 1) (34,35). Approximately 25% of the world's population suffers from anemia and Fe deficiency is its leading cause (50-60% affected).…”
Section: Malnutrition-a Hidden Hungermentioning
confidence: 99%
“…Although gaps exist in the understanding of the pathophysiological mechanisms underpinning the interaction between gut microbiota and bone, it has been hypothesized that dietary supplements, prebiotics (non-digestible dietary fibers stimulating selective bacterial growth), and probiotics (microorganisms that might confer a health benefit to the host) contribute to the intestinal microecological balance, which is important for bone health [23][24][25]. Indeed, dietary supplements and probiotics might play a role in the management of osteoporosis, in conjunction with the already-known medical and lifestyle interventions.…”
Section: Introductionmentioning
confidence: 99%
“…IBD can result in alterations in the composition of the gut microbiota, leading to changes in the secretion of particular shortchain fatty acids as well as changes in the lumenal pH within the intestines, thereby impairing calcium absorption and resulting in dysregulated bone metabolism that can further progress to cause osteoporosis. 13 The association between the intestinal microbiota and bone metabolism has been a topic of growing research interest in recent years, with several studies having found that modulating the gut microbiome can improve bone health and prevent bone calcium loss. 14,15 The gut flora plays a foundational role in both human health and disease, [16][17][18] with intestinal dysbiosis being linked to the development of obesity 19 and IBD.…”
Section: Introductionmentioning
confidence: 99%